THE BROWN BEAR IN THE NOVEL OF ION D. SÎRBU: FOLK-MYTHOLOGY IN THE SATIRICAL FABLE "THE DANCE OF THE BEAR" - POP, Ionucu (Studia Universitatis Babeș-Bolyai Philologia, 2022)
The Brown Bear in the Novel of Ion D. Sîrbu: Folk-Mythology in The Satirical Fable The Dance of the Bear. Ion D. Sîrbu’s last anthumous novel, The Dance of the Bear, subtitled A Novel for Children and Grandparents, displays a highly nuanced understanding and symbolization of the animal world. This study aims to analyse the novel which, as the title suggests, abounds in animal imaginary, by focusing on its fable-like characteristics and the elements of Romanian folklore incorporated by the main prose writer of the Sibiu Literary Circle. Like most of Sîrbu’s anthumous works, The Dance of the Bear anticipates the critical and satirical attitude towards the totalitarian regime(s) that would later define the better-known posthumous books of Ion D. Sîrbu. The Aesopic dimension of the novel is facilitated by the clever instrumentation of the animal reference. One such reference is that of the Romanian mythological fauna, in the analysis of which, Mihai Coman’s Romanian Traditional Mythology proves to be revealing. Article history: Received 14 February 2022; Revised 10 May 2022; Accepted 17 May 2022; Available online 30 June 2022; Available print 30 June 2022. REZUMAT. Ursul brun în romanul lui Ion. D. Sîrbu: Mitologie populară în fabula satirică Dansul Ursului. Ultimul roman antum al lui Ion D. Sîrbu, Dansul ursului, purtând subtitlul “Roman pentru copii și bunici”, demonstrează o înțelegere și o simbolizare foarte nuanțate a lumii animale. Acest articol își propune să analizeze romanul care, după cum sugerează și titlul, abundă în imaginar animal, punând accent pe caracteristicile sale de fabulă și pe elementele folclorului românesc încorporate de principalul prozator al Cercului Literar de la Sibiu. La fel ca majoritatea operelor antume ale autorului în cauză, Dansul ursului anticipează atitudinea critică și satirică față de regimurile totalitare care avea să definească ulterior cele mai cunoscute cărți postume ale lui Ion D. Sîrbu. Dimensiunea esopică a romanului este facilitată de instrumentarea inteligentă a referinței animale. O astfel de referință este cea a faunei mitologice românești, în analiza căreia lucrarea lui Mihai Coman, Mitologie populară românească se dovedește revelatoare. Cuvinte-cheie: Ion D. Sîrbu, Cercul Literar de la Sibiu, fabulă, mitologie populară românească, eco-etologie, literatură română postbelică, satiră